General-purpose systolic arrays - Johnson, K.T.; Hurson, A.R.; Shirazi, B. (Computer (Long Beach, Calif.), 1993)
The extension of systolic array architecture from fixed- or special-purpose architectures to general-purpose, SIMD (single-instruction stream, multiple-data stream), MIMD (multiple-instruction stream, multiple-data stream) architectures, and hybrid architectures that combine both commercial and FPGA (field-programmable gate array) technologies is chronicled. The authors present a taxonomy for systolic organizations, discuss each architecture's methods of exploiting concurrencies, and compare performance attributes of each. The authors also describe a number of implementation issues that determine a systolic array's performance efficiency, such as algorithms and mapping, system integration through memory subsystems, cell granularity, and extensibility to a wide variety of topologies.< >